PELATIHAN WIRAUSAHA KELOMPOK PEMUDA PENANGGULANGANBENCANA DI KAWASAN MERAPI, YOGYAKARTA - Astarika, Rina; Munadi, La Ode Muh.; Koso, Halija; Zumail, La Ode; Samiel, Edy; Khabiirun, Khabiirun; Mufakhir, La Ode Abul; Dewi, Fitria; Yaddi, Yamin; Sahaba, La Ode (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The purpose of community service activities for youth disaster management groups in the Merapi area is to improve entrepreneurial skills, introduce online promotional media, develop design and promotional skills, and train them in marketing products and services. The challenge faced by this group is how to improve their economic level even though their knowledge and skills are limited to natural disaster management. The methods of implementing this activity include providing motivation, instilling an entrepreneurial spirit, financial management training, graphic design training, and ongoing mentoring. This activity has succeeded in fostering an entrepreneurial spirit among youth in the Merapi area, improving their knowledge and skills, and connecting them with online media to market their products and services.